Challenges to trauma care delivery for Australian and New Zealand trauma clinicians. Issue 5 (May 2020) - Curtis, Kate; Gabbe, Belinda; Vallmuur, Kirsten; Martin, Katherine; Nahidi, Shizar; Shaban, Ramon Z.; Pollard, Cliff; Christey, Grant
Highlights: Perspectives of a diverse sample of trauma care professionals in Australia and New Zealand about their clinical practice challenges are presented. The most common clinical practice challenges relate to clinical management (in particular, blood product and fluid management in bleeding patients; identifying major older person trauma) and operationalisation of the trauma system (timely access to specialised care by improving referral and transfer processes). Trauma care professionals reported several clinical practice challenges where there was evidence to guide practice, but implementation was difficult, especially in uptake of existing evidence-based guidelines. The clinical practice challenges identified in this study should be the focus of efforts to generate evidence and translate evidence into practice for high quality and safe trauma care across Australian and New Zealand. Abstract: Introduction: The availability and implementation of evidence-based care is essential to achieving safe, quality trauma patient outcomes. Little is documented, however, about the challenges trauma clinicians face in their day-to day practice, or their views on the availability of evidence. This paper presents the most significant clinical practice challenges reported by multidisciplinary trauma care professionals in Australia and New Zealand, in particular those that may be resolved with focussed research or enhanced implementation activity. Methods: An exploratory survey of trauma professionals from relevant Australia and New Zealand professional organisations was conducted between September 2018 and February 2019 using the Snowballing Method. Participants were recruited via a non-random sampling technique to complete an online survey. Thematic analyses were conducted. Results: There were nine significant clinical practice challenge themes in trauma care, arising from 287 individual clinical practice challenges reported. The most reported being clinical management (bleeding, spinal, older patients) and operationalisation of the trauma system. There was no consensus as to the availability of evidence to guide each theme. Conclusion: Future research should seek to address the clinical practice challenge of Australian and New Zealand trauma community to enable safe, quality trauma patient outcomes.